On‐Chip Monolithically Integrated Ultraviolet Low‐Threshold Plasmonic Metal‒Semiconductor Heterojunction Nanolasers - Jia‐Yuan Sun; Duc Huy Nguyen; Jia‐Ming Liu; Chia‐Yao Lo; Yuan‐Ron Ma; Yi‐Jia Chen; Jui‐Yun Yi; Jian‐Zhi Huang; Hien Giap; Hai Yen Thi Nguyen; Chun‐Da Liao; Ming‐Yi Lin; et al. (Advanced Science, 2023)
Abstract The metal‒semiconductor heterojunction is imperative for the realization of electrically driven nanolasers for chip‐level platforms. Progress in developing such nanolasers has hitherto rarely been realized, however, because of their complexity in heterojunction fabrication and the need to use noble metals that are incompatible with microelectronic manufacturing. Most plasmonic nanolasers lase either above a high threshold (101‒103 MW cm−2) or at a cryogenic temperature, and lasing is possible only after they are removed from the substrate to avoid the large ohmic loss and the low modal reflectivity, making monolithic fabrication impossible. Here, for the first time, record‐low‐threshold, room‐temperature ultraviolet (UV) lasing of plasmon‐coupled core‒shell nanowires that are directly grown on silicon is demonstrated. The naturally formed core‒shell metal‒semiconductor heterostructure of the nanowires leads to a 100‐fold improvement in growth density over previous results. This unprecedentedly high nanowire density creates intense plasmonic resonance, which is outcoupled to the resonant Fabry‒Pérot microcavity. By boosting the emission strength by a factor of 100, the hybrid photonic‒plasmonic system successfully facilitates a record‐low laser threshold of 12 kW cm−2 with a spontaneous emission coupling factor as high as ≈0.32 in the 340‒360 nm range. Such architecture is simple and cost‐competitive for future UV sources in silicon integration.